2021
DOI: 10.1007/s00161-021-01050-y
|View full text |Cite
|
Sign up to set email alerts
|

Mathematical modeling of the elastic properties of cubic crystals at small scales based on the Toupin–Mindlin anisotropic first strain gradient elasticity

Abstract: In this work, a mathematical modeling of the elastic properties of cubic crystals with centrosymmetry at small scales by means of the Toupin–Mindlin anisotropic first strain gradient elasticity theory is presented. In this framework, two constitutive tensors are involved, a constitutive tensor of fourth-rank of the elastic constants and a constitutive tensor of sixth-rank of the gradient-elastic constants. First, $$3+11$$ 3 + 11 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
36
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 26 publications
(38 citation statements)
references
References 53 publications
2
36
0
Order By: Relevance
“…It is known that typical values of the length scale parameters of single crystals have the order of interatomic distance, i.e. within SSGET we have 𝑙 = 𝑙 1 = 𝑙 2 ≈ 1 Å (Lazar et al, 2021). Therefore, if the loading is applied at the atomically sharp edge of single crystal and provides the maximum remote tensile stress equals to 𝜏 11 = 1 MPa at distance 𝐿 = 1000𝑙 = 100 nm from the edge tip.…”
Section: Numerical Simulations For the Finite Size Wedgementioning
confidence: 98%
See 2 more Smart Citations
“…It is known that typical values of the length scale parameters of single crystals have the order of interatomic distance, i.e. within SSGET we have 𝑙 = 𝑙 1 = 𝑙 2 ≈ 1 Å (Lazar et al, 2021). Therefore, if the loading is applied at the atomically sharp edge of single crystal and provides the maximum remote tensile stress equals to 𝜏 11 = 1 MPa at distance 𝐿 = 1000𝑙 = 100 nm from the edge tip.…”
Section: Numerical Simulations For the Finite Size Wedgementioning
confidence: 98%
“…Components of the constitutive tensors 𝐂 and 𝐀 within Mindlin Form II can be defined as follows (dell'Isola et al, 2009;Lazar et al, 2021):…”
Section: Constitutive Equationsmentioning
confidence: 99%
See 1 more Smart Citation
“…In what follows we restrict ourselves to an isotropic behavior, so E$\mathbb {E}$ is zero, whereas C$\mathbb {C}$ and D$\mathbb {D}$ have the following representation [3, 25] double-struckCbadbreak=Cijkliiijikil,1emdouble-struckDgoodbreak=Dijmklniiijimikilin,$$\begin{equation} \mathbb {C} \eqcellsep =\eqcellsep \mathbb {C}_{ijkl}\mathbf {i}_i\otimes \mathbf {i}_j\otimes \mathbf {i}_k\otimes \mathbf {i}_l,\quad \mathbb {D} =\mathbb {D}_{ijmkln}\mathbf {i}_i\otimes \mathbf {i}_j\otimes \mathbf {i}_m\otimes \mathbf {i}_k\otimes \mathbf {i}_l\otimes \mathbf {i}_n, \eqbreak \end{equation}$$ Cijklbadbreak=λδijδklgoodbreak+μ(δikδjl+δilδjk),$$\begin{equation} \mathbb {C}_{ijkl}\eqcellsep =\eqcellsep\lambda \delta _{ij}\delta _{kl} +\mu (\delta _{ik}\delta _{jl}+\delta _{il}\delta _{jk}), \end{equation}$$ Dijmkln=a12δijδkmδ…”
Section: Governing Equationsmentioning
confidence: 99%
“…Let us assume that the gradient moduli of crystallites are very small (G gr ≈ 0) and has spherical shape. The first assumption is realistic and it bases on the known results of atomistic calculations for the gradient moduli of monocrystals, for which it was found that the the length scale parameters of SGET has sub-nanometer order [38,39]. The assumption about spherical shape of grains is just an approximation of the model that is widely used within classical micromechanics [2,33].…”
Section: Solution For the Cauchy-type Spherical Grainsmentioning
confidence: 99%